2006
DOI: 10.1007/s00330-006-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between histologic thickness of tongue carcinoma and thickness estimated from preoperative MRI

Abstract: Several studies have shown that the thickness of tongue carcinoma is related to prognosis and to the likelihood of cervical node metastases. We investigated whether preoperative estimates of tumor thickness and volume, as determined from magnetic resonance imaging (MRI), correlated with histologic thickness and might therefore predict the presence of neck metastases. We assessed relationships between histologic tumor thickness and MRI tumor thickness and volume in a retrospective series of 33 patients with squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 33 publications
12
67
2
3
Order By: Relevance
“…[19][20][21] MR imaging thickness in patients with metastatic lymph nodes tended to be greater than that in metastases-free patients, though the difference was not significant between patients with and without metastasis. 21 Tongue carcinoma varies in the tumor shape (reductive or expansive) and in the growth pattern (endophytic or exophytic). Therefore, how far tumor cells invade and which structures these cells infiltrate, rather than tumor thickness, may be important.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…[19][20][21] MR imaging thickness in patients with metastatic lymph nodes tended to be greater than that in metastases-free patients, though the difference was not significant between patients with and without metastasis. 21 Tongue carcinoma varies in the tumor shape (reductive or expansive) and in the growth pattern (endophytic or exophytic). Therefore, how far tumor cells invade and which structures these cells infiltrate, rather than tumor thickness, may be important.…”
mentioning
confidence: 72%
“…In MR imaging, the structures of normal tongue architecture and the oral tongue carcinoma can be clearly shown, and coronal MR imaging can also be used to satisfactorily measure the thickness of oral tongue carcinoma. 19 Preda et al 21 found that tumor thickness of tongue carcinoma on MR imaging correlated directly with the histologic tumor thickness, and mean tumor thickness in patients with lymph node metastases was greater than that of those without metastases; but the difference did not reach significance in 33 patients. In our 43 patients, the tumor thickness was significantly (P Ͻ .05) associated with lymph node metastases, and the thickness was a statistically significant predictor of lymph node metastases in multivariate logistic re- gression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…7 The lateromedial thickness taken in axial MR plane is used as the precise measurement for assessing the tumors from the lateral border of the tongue. [8][9][10][11] Another study by Okura et al established that a tumour with thickness > 9.7 mm as a significant predictor for nodal metastasis. 8 The other predictors for staging the tumor is to assess the involvement of muscles with or without crossing the midline, extension into floor of mouth, valleculae, pre epiglottic space and the hyoid bone.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…8 The other predictors for staging the tumor is to assess the involvement of muscles with or without crossing the midline, extension into floor of mouth, valleculae, pre epiglottic space and the hyoid bone. [9][10][11] The involvement of valleculae, pre epiglottic space and hyoid bone indicates relative contra indication for surgical resection.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…Accordingly, multi-sliced imaging techniques should be useful and convenient. Recently, the correlation between histologic tumor thickness and magnetic resonance imaging (MRI) tumor thickness was demonstrated (Iwai et al 2002;Lam et al 2004;Preda et al 2006). Then MRI tumor thickness seems to become a candidate of occult metastatic predictor, although these studies did not reach to demonstrate the relation with MRI tumor thickness and regional metastases.…”
Section: Predictors Of Occult Metastasesmentioning
confidence: 99%